An assessment of commuters’ perceptions of safety and comfort levels of ‘women-only coach’: the case study of KTM Komuter Malaysia - Bachok, Syahriah; Mohamed Osman, Mariana; Murad, Mirahida; Ibrahim, Mansor (Elsevier, 2014)

(untitled)
Ideally, cities of developing countries and their public transportation services need to be sensitive to the quality of services rendered. In this context, this study assessed the commuters' perceptions towards Women-Only Coach services by the KTM Komuter. KTM Komuter, is a suburban heavy rail service provided by the company Keretapi Tanah Melayu Berhad (KTMB) in Klang Valley, Malaysia. This research centers around the experiences of users of Women-Only Coach, a segmented sub-service especially provided for the safety and comfort of female riders. An on-board survey was conducted among the commuters of Women Only Coach who regularly used the women coach only for travelling. A systematic cluster sample of 550 respondents was taken for data collection, 513 of which were analyzed following a data cleaning process. Descriptive and inferential analyses have been applied to the date. Based on the analyses, it was found that majority of the female commuters were aware about the provision of Women- Only Coach. Moreover, a significant number of respondents claimed that there was an absence of security personnel at Women- Only Coach to monitor the safety of the coach and the majority of these respondents also felt insecure in the presence of male passengers on-board Women-Only Coach. Findings also suggested that a significant number of respondents were not satisfied with the current capacity of Women-Only Coach. The research undertaken had also confirmed the persistence of three major problems related to Women-Only Coach which were (i) the lack of enforcement in Women-Only Coach, (ii) the insufficient capacity to accommodate increasing demand and (iii) the poor visual quality of the signs indicating and distinguishing Women-Only Coach from the other rail-cars. The research also recommended strategic and immediate areas warranting improvements on board Women-Only Coach so as to enhance the current safety and comfort levels during journey makings among the existing users.